A Six Degrees-of-Freedom Flight Dynamics Simulation Tool of Launch Vehicles - Silveira,Guilherme da (2015)
ABSTRACT: The use of digital simulation has become an essential activity during the development and operation of launch vehicles, due to the complexity of such systems. Of particular interest is the flight dynamics simulation, which investigates the behavior of the vehicle in flight subjected to forces and moments. This work presents a simulation tool suited to perform six degrees-of-freedom flight dynamics investigations of launch vehicles. Developed at the Instituto Nacional de Pesquisas Espaciais (INPE) and the Instituto de Aeronáutica e Espaço (IAE) in Brazil, the tool was implemented following the requirement for flexibility, so that it can be used to simulate different types of launch vehicles. The assessment of the vehicle performance and the vehicle payload capacity are some examples of analysis that can be performed with the tool. A modular programming strategy was employed to assure the tool flexibility. Therefore, the models presented in the tool were implemented as separate modules. The combination of these models can originate flight models of different launch vehicles. Two flight scenarios of Brazilian rockets were simulated and the results were verified against simulation tools already employed by aerospace community. The developed tool showed good agreement with respect to the simulators used to perform the comparison.